Analisis Finansial Pengolahan Terasi Udang Skala Rumah Tangga oleh Isteri Nelayan di Binaloka Kelurahan Samkai Kabupaten Merauke - Sajriawati, Sajriawati; Amir, Astaman (MuJAgri: Musamus Journal of Agribusiness, 2021)
This study entitled financial analysis of household-scale shrimp paste processing by fishermen's wife at Binaloka of Samkai Village in Merauke Regency aims to determine the feasibility and benefits of shrimp paste processing business. The research was conducted for 3 (three) months, from September to November 2020. Respondents of this study were 5 people who process shrimp paste on a household scale. Respondents were selected based on the purposive sampling method because of the limited research time and costs. Data analysis was performed by calculating total costs, operating income, and business profits. Based on the results of the study, it was concluded that the household scale shrimp paste processing business by fishermen's wife in Binaloka, Samkai Village, Merauke Regency, has an R / C ratio of 2.04 so that it has a feasible or profitable category. The profit obtained is Rp. 1,549,133 per production. Keywords: Financial analysis, shrimp paste, fisherman wife, Binaloka Merauke